Hot Student Stories
top-5-grammar-and-spelling-checkers-to-rock-in-2019

What substitution should be used to rewrite 6(x + 5)2 + 5(x + 5) – 4 = 0 as a quadratic equation? u = (x + 5) u = (x – 5) u = (x + 5)2 u = (x – 5)2

Dana Keller

in Mathematics

follow
followin
1 answer
12 views

1 answer


Kaitlin Dean on November 14, 2018

So the question is, what substitution should we use to rewrite 6(x+5)^2 + 5(x+5) - 4 = 0 to get a quadratic equation. A quadratic equation has a form ax^2 + bx + c = 0 So that we have to achieve our original equation for that form. To do that we must substite (x+5)=u and we obtain: 6u^2 + 5u - 4 = 0. and the correct answer is u=(x+5).


Add you answer